Use of Systemic Glucocorticoids and Risk of Prostate Adenocarcinoma: Evidence From a Danish Population‐Based Case–Control Study - Elea Olivier; Blánaid Hicks; Morten Olesen; Agnès Fournier; Gianluca Severi; Anton Pottegård; Manon Cairat (Cancer Medicine)
ABSTRACT Background Glucocorticoids may promote prostate cancer by reducing apoptosis and the immune response, or prevent it by reducing inflammation, inhibiting androgens, and limiting cell proliferation. However, epidemiological evidence is limited. Thus, this study aimed to assess the association between systemic glucocorticoids and prostate cancer risk within the Danish registries. Methods A nationwide case–control study was conducted using Danish healthcare registries. Men with a primary prostate adenocarcinoma diagnosis between 2001 and 2018 were identified as cases (n = 56,575). For each case, 10 controls were randomly selected from the general population, matched on age and calendar time. Exposure to systemic glucocorticoid was identified via the national prescription registry from 1995 onwards. Ever users of systemic glucocorticoids were defined as at least 2 filled prescriptions, and long‐term use as filled prescriptions equivalent to ≥ 1000 defined daily doses (DDDs). Conditional logistic regressions were performed to calculate odds ratios (ORs) and 95% confidence intervals for the association between systemic glucocorticoid use and prostate cancer risk. Results Twelve percent of men had ever been exposed to systemic glucocorticoids. No association was observed between ever and long‐term use of systemic glucocorticoids and prostate cancer risk [OR = 1.03 (1.00–1.06) and OR = 1.02 (0.92–1.14), respectively], compared with never use. However, an inverse association was observed with the highest use category (> 1500 DDDs) [OR = 0.86 (0.74–0.99)], though without evidence of a dose–response relationship [OR per 500 DDDs = 0.98 (0.95–1.01), p = 0.18]. Associations did not differ by prostate cancer stage. Conclusion This large nationwide nested case–control study suggested no evidence of a higher risk of prostate adenocarcinoma associated with systemic glucocorticoid use.